1 × 2 × 3 1 + 2 × 3 × 4 1 + 3 × 4 × 5 1 + 4 × 5 × 6 1 + ⋯ = ?
Try a similar and easier problem here .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
S = 1 × 2 × 3 1 + 2 × 3 × 4 1 + 3 × 4 × 5 1 + ⋯ = k = 1 ∑ ∞ k ( k + 1 ) ( k + 2 ) 1 = k = 1 ∑ ∞ 2 1 ( k 1 − k + 1 2 + k + 2 1 ) = 2 1 ( k = 1 ∑ ∞ ( k 1 − k + 1 1 ) − k = 1 ∑ ∞ ( k + 1 1 − k + 2 1 ) ) = 2 1 ( 1 1 − 2 1 ) = 4 1 = 0 . 2 5
We have
( n − 1 ) ( n ) ( n + 1 ) 1 = n ( n 2 − 1 ) 1 = n 2 − 1 n − n 1 = ( n − 1 ) ( n + 1 ) n − n 1 = 2 1 ( n − 1 1 + n + 1 1 ) − n 1 = 2 1 ( ( n − 1 1 − n 1 ) + ( n + 1 1 − n 1 ) ) .
Thus,
n = 2 ∑ ∞ ( n − 1 ) ( n ) ( n + 1 ) 1 = n = 2 ∑ ∞ ( 2 1 ( ( n − 1 1 − n 1 ) + ( n + 1 1 − n 1 ) ) ) = 2 1 ( 1 − 2 1 ) = 4 1 .
For any positive integer n, 1/[(n).(n+1).(n+2)] = (1/2)[1/(n)(n+1) - 1/(n+1)(n+2)]. So 1/(1.2.3) + 1/(2.3.4) + 1/(3.4.5) + ....= (1/2)[1/(1.2) - 1/(2.3) + 1/(2.3) - 1/(3.4) + 1/(3.4) - 1/(4.5) + ........] = (1/2)[1/(1.2)] = 0.25
Problem Loading...
Note Loading...
Set Loading...
Relevant wiki: Telescoping Series - Sum
By virtue of n ( n + 1 ) ( n + 2 ) 1 = 2 1 ( n ( n + 1 ) 1 − ( n + 1 ) ( n + 2 ) 1 ) , we have S = n = 1 ∑ ∞ n ( n + 1 ) ( n + 2 ) 1 = 2 1 n = 1 ∑ ∞ ( n ( n + 1 ) 1 − ( n + 1 ) ( n + 2 ) 1 ) = 2 1 ( 1 × 2 1 − 2 × 3 1 + 2 × 3 1 − 3 × 4 1 + ⋯ ) = 4 1 = 0 . 2 5 .